Immobilization strategies for organic semiconducting conjugated polymers - Freudenberg, Jan; Bunz, Uwe H. F. (Chemical reviews, 2018)
This Review details synthetic routes toward and properties of insoluble polymeric organic semiconductors obtained through desolubilization strategies. Typical applications include fixation of donor-acceptor bulk-heterojunction morphologies in organic photovoltaic cells, cross-linking of charge transport materials and active emitters in light emitting diodes or similar devices, and immobilization of morphologies in field effect transistors. A second important application is the structuring of organic semiconductors, using them as photoresists. After desolubilization, removal of the nonirradiated resist leads to elevated, micron-sized features of the semiconductor. In this Review, different strategies for desolubilization are covered. By photochemical or thermal cleavage of solubility-mediating groups such as esters, sulfonium salts, amides, ethers, and acetals or by retro-Diels-Alder reactions, volatile elimination products and the insoluble semiconductor are formed. In another case, desolubilization is achieved by cross-linking via functional groups present in the polymer side chains including vinyl, halide, silicone, boronic acid, and azide functionalities, which polymerize thermally or photochemically. Alternatively, small molecular additives such as photoacids, oligothiols, or oligoazides result in network formation in combination with compatible functional groups present in the immobilizable polymers. Advantages and disadvantages of the respective methods are discussed.